Prevalence and mortality rate of healthcare-associated infections among COVID-19 patients: a retrospective cohort community-based approach - Fakhreddine, Soha; Fawaz, Mirna; Hassanein, Salwa; Al Khatib, Alissar (Frontiers in Public Health, 2023)
The prevalence of HAI among COVID-19 patients ranged between 4.8% and 42.8% with the highest occurrence observed in critically ill patients. The present study aimed to evaluate the clinical features of HAI in severe and critical COVID-19 patients, their microbiological characteristics, and the attributable risk factors. Methods: This is an analytical observational, retrospective single-center, cohort study that included 723 patients with severe-critical COVID-19 admitted to Saint George Hospital between September 2020 and February 2021. Data collection included demographic variables (sex, age), comorbidities, laboratory findings, HAI types and agents, COVID-19 treatment modalities, hospitalization settings, length of stay, and mortality rate.Data was analyzed using SPSS version 25. Results: The prevalence of patients developing HAI was 7.3% (53 of 723). Five types of nosocomial bacterial infections were tracked noting ventilatorassociated pneumonia (41.26%), catheter-associated urinary tract infection (28.6%), hospitalacquired pneumonia (17.44%), catheter-related bloodstream infection (6.35%), and bloodstream infection (6.35%). Binary logistic analysis showed that HAI are statistically affected by four factors noting patients' age (p = 0.039), Length of Stay (p < 0.001), BIPAP (p = 0.019), and mechanical ventilation (p < 0.001). The risk of having HAI increases 3.930 times in case of mechanical ventilation, 2.366 times in case of BIPAP, 1.148 times when the LOS increases 1 day, and 1.029 times when the age is higher with 1 year. Conclusion: Since the prevalence of HAI is high among severe and critical Covid-19 patients, it is important to prepare a treatment with diagnostic, preventative, and control measures for this infection.